2016
DOI: 10.1039/c5ra20676f
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of coronatine as a bacterial virulence factor against plants: possible COI1–JAZ-independent role

Abstract: A phytotoxin coronatine has a dual mode of action, triggering stomatal reopening through COI1–JAZ-dependent and independent pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…Xie's group reported that the amino acid conjugates, JA-Leu, JA-Val, JA-Met, and JA-Ala, function as endogenous jasmonates as well as JA-Ile [58]. This result will be useful for further molecular design of COI1-JAZ agonists, the spatial limitations of the ligand-binding pocket of COI1 having been demonstrated-a finding supported by the molecular docking study by Ueda' s group [59].…”
Section: Other Chemicals Involved In the Tuned Regulation Of Jasmonatmentioning
confidence: 74%
“…Xie's group reported that the amino acid conjugates, JA-Leu, JA-Val, JA-Met, and JA-Ala, function as endogenous jasmonates as well as JA-Ile [58]. This result will be useful for further molecular design of COI1-JAZ agonists, the spatial limitations of the ligand-binding pocket of COI1 having been demonstrated-a finding supported by the molecular docking study by Ueda' s group [59].…”
Section: Other Chemicals Involved In the Tuned Regulation Of Jasmonatmentioning
confidence: 74%
“…We therefore used a stereochemical isomer of 3 to develop a subtype-selective PPI stabilizer between COI1 and JAZ. Optically pure samples of the building blocks of 3 , (+)-coronamic acid (CMA, 4 ) 29 , and (+)-coronafacic acid (CFA, 5 ) 30 , were coupled to give naturally occurring 3 , the enantiomer ent 3 , and the stereochemical hybrid isomers, CFA- ent CMA ( 6 ) and ent CFA-CMA ( ent 6 ), respectively (Fig. 1a ) 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The structure of coronatine consists of coronafacic acid (+)-CFA (an analog of MeJA) and coronamic acid, joined by an amide bond between the acid group of CFA and the amino group of coronamic acid, and so (+)-CFA could be considered as a structural mimic of (+)-7-iso-JA (Supplemental Fig. S8; Egoshi et al, 2016). Treatment of wild type with (+)-CFA dramatically suppressed LR formation, with only slight effects on primary root growth (Fig.…”
Section: Coronafacic Acid Was An Lr-preferential Auxin Inhibitormentioning
confidence: 99%